The fundamental principles of Islamic law in the digital era: An ushul fiqh and maqashid Sharia approach - Harefa, Safaruddin (Journal of Islamic Law on Digital Economy and Business, 2025)
Purpose – This study aims to explore and formulate the fundamental principles of Islamic law in addressing contemporary digital transformation by integrating the methodologies of ushul fiqh and maqashid Sharia. It responds to the need for a dynamic yet normatively grounded Islamic legal framework capable of regulating emerging issues, such as digital contracts, e-money, artificial intelligence, and virtual marriage. Methodology – This study employed a qualitative normative legal method using doctrinal analysis. The data were drawn from classical jurisprudence, contemporary fatwas, academic journals, and case studies on digital law. Sources were purposively selected for their relevance to Islamic legal responses to digital issues. The analysis used conceptual mapping and thematic interpretation guided by ushul fiqh and maqashid Sharia principles. Findings – The findings indicate that ushul fiqh tools, such as qiyas, istihsan, and maslahah mursalah, offer structured adaptability for addressing digital innovation within a Sharia-compliant framework. In parallel, maqashid Sharia strengthens the ethical dimension and enhances societal relevance, particularly by preserving values such as justice, intellect, and wealth. The combined application of both approaches enables the reconstruction of legal reasoning that is faithful to tradition and responsive to modern needs. Implications – This study contributes to the development of contemporary Islamic jurisprudence by proposing an integrative model that bridges classical norms and digital governance. It provides a basis for producing ethical fatwas, Sharia-compliant digital policies, and inclusive legal innovation. Originality – This research uniquely integrates ushul fiqh and maqashid Sharia to reconstruct Islamic legal reasoning in the digital era, addressing a critical gap between tradition and technological transformation.